Sobre la domesticación obrera a través de la vivienda higiénica. Algunos hallazgos (Santiago, 1931-1936) - Diego Morales Barrientos (Les Cahiers ALHIM)
Through the elite's perspective, the low-cost and hygienic household was a tool to improve the deficient living conditions that the popular and working-class sectors were under in big cities. Also, it was a means for cultural transformation of everyday policies. Stemming from this, the modeling and disciplinary capacity that hygienic living had over various working sectors has been discussed under various lenses. Through the analysis of some hygienic neighborhoods built in Santiago between the decades of the 1920s and 1930s it is possible to recognize circumstances that determined the constant yearly mobility of dozens of their occupants. And, by proxy, it is possible to determine the capacity that these residential complexes had to change the way of living of the working class family.